PRODUCTION OF ALTERNATIVE PLANT MILK (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The reason for the growing popularity of plant-based milk is that an increasing number of people refuse animal products. Oat milk is much easier to absorb than nuts, so it has a relatively large amount of beta-glucan, protein, amino acids, lipid and starch components, therefore, it benefits the body.